Reactions of the Lipid Hydroperoxides With Aminic Antioxidants: The Influence of Stereoelectronic and Resonance Effects on Hydrogen Atom Transfer - Li, Yu-Zhen; Zhou, Xiao-Lu; Huo, Bao-Qi; Chen, De-Zhan; Liu, Zhao-Hua; Sheng, Xie-Huang (Frontiers in Chemistry, 2019)
Aminic radical-trapping antioxidants (RTAs), as one of the most important antioxidants, have not received sufficient attention yet. But, an increasing number of aminic RTAs have been identified as ferroptosis inhibitors in recent years, which can potentially mediate many pathological states including inflammation, cancer, neurodegenerative disease, as well as ocular and kidney degeneration. This highlights the importance of aminic RTAs in the field of medicine. Herein, we systematically explored the radical scavenging mechanism of aminic RTAs with a quantum chemical method, particularly emphasizing the role of stereoelectronic factors and resonance factors on the transfer of H-atom and the stability to one-electron oxidation. These theoretical results elucidate the diversity of free radical scavenging mechanisms for aminic RTAs, and has significant implications for the rational design of new aminic RTAs.